Utilization and Impact of Peer-Support Programs on Police Officers’ Mental Health - Milliard, Beth (Frontiers in Psychology, 2020)
Police officer suicide rates hit an all-time high in the province of Ontario, Canada, in 2018. Sadly, this statistic is somewhat unsurprising, as research has shown that police officers suffer from higher rates of mental health disorder diagnoses compared to the general public. One key reason for the elevated levels of suicide and other mental health issues among police officers is the stigma associated with seeking help. In an attempt to address these serious issues, Ontario’s police services have begun to create internal peer support programs as a way of supporting their members. The present research explores the experiences of police officers serving as peer-support team members, particularly with regards to the impacts of peer support. In addition, this research also examines the importance of discussing shared experiences regarding a lack of provincial standards with credible peers. This study utilized a phenomenological, qualitative approach, with data collection consisting of face-to-face interviews with 9 police officers serving on the York Regional Police’s peer-support team. The findings revealed that peer support is more than just a “conversation”; rather, it is instrumental in enhancing mental health literacy among police officers, and it significantly contributes to stigma reduction. The findings also revealed that internal policy demonstrated an organizational commitment to mental health and peer-support, and that a provincial standard is necessary to ensure best practices and risk management in the creation and maintenance of peer-support programs.